b4 2018.06.02 “8.12”Tianjin Explosion and Industrial NC.pdf - Gill, Philip (Cranfield University, 2023)
“8.12”Tianjin Explosion and Industrial NC Peng Huan Sichuan Nitrocell Corp. P.R. of China
Keywords: 'nitrocellulose'